2011
DOI: 10.1103/physrevb.83.075403
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and abstraction reactions of HCl on a single Si(100) dangling bond

Abstract: On a Si(100)-(2x1) surface with abundant dangling bonds, reaction of HCl molecules at room temperature is dominated by exothermic dissociative adsorption of H and Cl on two adjacent dangling bonds. This co-adsorption reaction is blocked for an isolated dangling bond, yet surprisingly endothermic H or Cl abstractive adsorption occurs, as observed by in situ scanning tunneling microscopy. On an isolated dimer dangling bond pair, co-adsorption of H and Cl is common as expected, but adsorption of a pair of abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…18,19 These structured dangling bonds can be promising candidates for charge qubits 20 and can also be used for chemisorption of molecules such as I 2 21 and HCl. 22 Controllable manipulation of adatoms, molecules, nanoclusters, and dopants has already been achieved on/in surfaces of metals, semiconductors, and insulators. 5,23À29 However, while controlled lateral manipulation of individual vacancies across a surface lattice has been predicted theoretically to be possible using an atomic force microscope, 30 it has not been achieved experimentally.…”
mentioning
confidence: 99%
“…18,19 These structured dangling bonds can be promising candidates for charge qubits 20 and can also be used for chemisorption of molecules such as I 2 21 and HCl. 22 Controllable manipulation of adatoms, molecules, nanoclusters, and dopants has already been achieved on/in surfaces of metals, semiconductors, and insulators. 5,23À29 However, while controlled lateral manipulation of individual vacancies across a surface lattice has been predicted theoretically to be possible using an atomic force microscope, 30 it has not been achieved experimentally.…”
mentioning
confidence: 99%
“…H-passivated Si(100) has been the standard substrate for atomically precise device fabrication due in large part to its ease of lithographic patterning and the use of PH 3 and, more recently, B 2 H 6 and AsH 3 for doping reactions. , H-based dopant precursors experience no driving force to react with the H passivation layer. In contrast, the use of BCl 3 presents a possible pathway for reaction with the H passivation layer through abstraction , or nucleophilic attack of the Cl on the H, thereby compromising the selectivity required for device fabrication with good pattern fidelity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…9,38 Hbased dopant precursors experience no driving force to react with the H passivation layer. In contrast, the use of BCl 3 presents a possible pathway for reaction with the H passivation layer through abstraction 37,39 or nucleophilic attack of the Cl on the H, thereby compromising the selectivity required for device fabrication with good pattern fidelity.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Earlier experiments of HCl and HBr on Si(100) were performedin contrast to the present workat saturation coverage 21−24 or on a hydrogenated surface. 25 While dissociative attachment was found to be a major pathway, previous authors found evidence of the abstraction of single atoms, H or Cl, by the surface. Adsorbate−adsorbate interactions were investigated to explain the pattern of longrange ordering of Cl at high coverage.…”
Section: Introductionmentioning
confidence: 98%